2010
DOI: 10.1111/j.1574-695x.2010.00702.x
|View full text |Cite
|
Sign up to set email alerts
|

TheyddV-dosoperon controls biofilm formation through the regulation of genes encoding curli fibers' subunits in aerobically growingEscherichia coli

Abstract: In bacteria, intracellular amounts of the signal molecule cyclic di-GMP (c-di-GMP) are determined by biosynthetic enzymes, or diguanylate cyclases (DGCs), and degradative enzymes, or c-di-GMP phosphodiesterases (c-PDEs). In Escherichia coli, the production of curli fibers, an important adhesion factor, responds to c-di-GMP. The yddV-dos operon, which encodes a DGC and a c-PDE acting as a protein complex, is highly expressed at a low growth temperature and in the stationary phase, i.e. conditions that also stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…5). Mutations in either the pgaA or the yddV gene resulted in a 2.5-fold reduction in surface adhesion in the MG1655 background, in agreement with previous observations (Wang et al, 2004;Tagliabue et al, 2010).…”
Section: Regulation Of Pgaabcd Expression By Dgcssupporting
confidence: 91%
See 2 more Smart Citations
“…5). Mutations in either the pgaA or the yddV gene resulted in a 2.5-fold reduction in surface adhesion in the MG1655 background, in agreement with previous observations (Wang et al, 2004;Tagliabue et al, 2010).…”
Section: Regulation Of Pgaabcd Expression By Dgcssupporting
confidence: 91%
“…Recently, we have shown that YddV can affect the expression of curli-encoding genes (Tagliabue et al, 2010), which, however, are extremely sensitive to perturbations in intracellular c-di-GMP concentrations (Sommerfeldt et al, 2009). In this work, we show that overexpression of YddV, but not of other DGCs, stimulates production of poly-Nacetylglucosamine (PNAG), an EPS able to promote biofilm formation, by triggering expression of pgaABCD, the PNAG biosynthetic operon.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…A salient example is that of HIF-1, which affects mammalian development, metabolism, and tumor formation in response to limitation for molecular oxygen and other redox cues (41,42). Although PAS-domain-dependent, redox-sensitive regulation of exopolysaccharide production and biofilm development have been reported for selected nonpathogenic bacteria (43)(44)(45), the observations presented herein extend this model to the morphogenetic control of the pathogen P. aeruginosa, and specifically to the effects of endogenously produced electron shuttles (Fig. 5E).…”
Section: Colony Matrix Distribution Phenotypes Suggest That Phenazinementioning
confidence: 99%
“…Regulation of curli-encoding genes is extraordinarily complex and responds to a combination of environmental cues, such as low growth temperature (¡30 u C), low osmolarity, slow growth and oxygen availability (Römling et al, 1998a;Gerstel & Römling, 2001Tagliabue et al, 2010a). The signal molecules cAMP (Zheng et al, 2004) and c-di-GMP (Kader et al, 2006;Weber et al, 2006), as well as intracellular concentration of pyrimidine nucleotides (Garavaglia et al, 2012), also have a strong impact on curli gene expression.…”
Section: Introductionmentioning
confidence: 99%